Implementasi Sistem Monitoring Jaringan Menggunakan Libre Nms Pada Kecamatan Tarik - Adi Putra, Lutfi; Alfan Rosid, Mochamad; Setiawan, Hamzah; Eviyanti, Ade (Indonesian Journal of Applied Technology, 2024)
Network monitoring is needed to find out the various types of equipment and systems that are connected. LibreNMS is one of network monitoring system that can make it easier for administrators to monitor the network and if there are any problems it can be resolved immediately. The features provided are numerous, making it easier to monitor network performance available and ready to use. This study aims to build a network monitoring system in Kecamatan Tarik using LibreNMS. The test results show if LibreNMS can show the condition of the network system and the use of various equipment which is properly monitored.